2017
DOI: 10.1099/mic.0.000422
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor analysis of eepR mutant defects reveals coordinate regulation of secondary metabolites and serralysin biosynthesis by EepR and HexS

Abstract: The EepR transcription factor positively regulates secondary metabolites and tissue-damaging metalloproteases. To gain insight into mechanisms by which EepR regulates pigment and co-regulated factors, genetic suppressor analysis was performed. Suppressor mutations that restored pigment to the non-pigmented ∆eepR mutant mapped to the hexS ORF. Mutation of hexS also restored haemolysis, swarming motility and protease production to the eepR mutant. HexS is a known direct and negative regulator of secondary metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The CRP and HexS transcription factors are potent inhibitors of secondary metabolite biosynthesis in strain PIC3611 and other strains, such that crp and hexS mutants are more highly pigmented than the isogenic wild-type strains (Kalivoda et al 2010; Stella et al 2012; Stella and Shanks 2014; Shanks et al 2017b). It was hypothesized that HexS and CRP were responsible for inhibiting the prodigiosin production at 37°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CRP and HexS transcription factors are potent inhibitors of secondary metabolite biosynthesis in strain PIC3611 and other strains, such that crp and hexS mutants are more highly pigmented than the isogenic wild-type strains (Kalivoda et al 2010; Stella et al 2012; Stella and Shanks 2014; Shanks et al 2017b). It was hypothesized that HexS and CRP were responsible for inhibiting the prodigiosin production at 37°C.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, it was determined that the transcription factor genes eepR and pigP were more highly expressed in crp and hexS mutants and that EepR and PigP were positive regulators of pig transcription in S. marcescens and another Serratia species (Fineran et al 2005; Shanks et al 2013; Stella et al 2015; Shanks et al 2017a). A model depicting the interaction between these transcription factors and the pig operon is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, many studies have been studied to analyze the metabolic regulatory network of prodigiosin synthesis. Besides the well-studied pig gene cluster, a total of 14 genes, associated with prodigiosin synthesis in S. marcescens , a few other genes that play important roles in prodigiosin synthesis in S. marcescens have also been investigated, including genes copA (Williamson et al, 2006b), crp (Stella and Shanks, 2014), hexS (Stella et al, 2012), rssB (Horng et al, 2010), spnR (Horng et al, 2002), eepR (Shanks et al, 2017), pigP (Shanks et al, 2013), smaI (Coulthurst et al, 2006), gumB (Stella et al, 2018), and rsbR (Lee et al, 2017). In this study, BVG90_02415 ( dacA ) gene encoding D-Ala-D-Ala carboxypeptidase DacA, a negative regulator of prodigiosin production, was screened by constructing the insertion mutant library of Tn 5G transposon.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the pigC gene encodes the terminal condensing enzyme PigC that condenses MAP and MBC to prodigiosin (Williamson et al, 2006a). In S. marcescens , the synthesis of prodigiosin is also controlled by several transcriptional regulators, including positive regulators EepR (Shanks et al, 2017), PigP (Shanks et al, 2013), SmaI (Coulthurst et al, 2006), GumB (Stella et al, 2018), and RbsR (Lee et al, 2017), and negative regulators CopA (Williamson et al, 2006b), CRP (Stella and Shanks, 2014), HexS (Stella et al, 2012), RssB (Horng et al, 2010), and SpnR (Horng et al, 2002). Among them, HexS, EepR, PigP, and RssB regulators directly bind to the promoter regions of the prodigiosin-associated pig operon, and thus affect the synthesis of prodigiosin.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the metabolic regulation network of prodigiosin biosynthesis in S. marcescens have revealed that pigABCDEFGHIJKLMN genes were involved in the biosynthetic pathway of prodigiosin synthesis ( Supplementary Figure S1 ) ( 1 ). Also, it is reported that prodigiosin biosynthesis in S. marcescens was widely regulated by a number of transcription factors including positive regulators EepR ( 6 ), PigP ( 7 ), GumB ( 8 ) and RbsR ( 9 ), and negative regulators MetR ( 10 ), SpnR ( 11 ), CopA ( 12 ), CRP ( 13 ), HexS ( 14 ), RssB ( 15 ), RcsB ( 16 , 17 ) and SmaR ( 18 ).…”
Section: Introductionmentioning
confidence: 99%